PENGUATAN KAPASITAS UMKM MASCOT LADA MELALUI PENDEKATAN PARTICIPATORY EMPOWERMENT - B Betri; Maidiana Astuti Handayani; Dewi Puspasari; Dimas Andrean (LPPM Universitas Nusa Mandiri, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in supporting regional economic growth; however, many still encounter challenges in financial management, production standardization, and digital marketing. These issues were identified in Mascot Lada MSME in Palembang City, Indonesia. A preliminary assessment involving 30 MSME participants revealed that only 20% regularly maintained financial records, 16.7% prepared simple financial reports, 23.3% implemented production standard operating procedures (SOPs), and only 40% had market reach beyond the local area. This community service program aimed to strengthen business management capacity, improve product quality, and expand digital marketing through a participatory community empowerment approach. The program was implemented through training, hands-on practice, and continuous mentoring in financial recordkeeping, social media and marketplace management, product packaging, and product photography using a mini studio. The results demonstrated significant improvements in the partner's business capacity. Financial recordkeeping increased from 20% to 80%, preparation of financial reports from 16.7% to 70%, implementation of production SOPs from 23.3% to 70%, packaging quality from 30% to 80%, social media utilization from 70% to 90%, and market reach beyond the local area from 40% to 70%. These findings indicate that participatory assistance supported by appropriate technology effectively enhances managerial capacity, product competitiveness, and market expansion of MSMEs.